Aplikasi Styrofoam Sebagai Absorpsi Bunyi - Allif Silfiyana Rohman; Agus Yulianto; Upik Nurbaiti (Jurnal Teori dan Aplikasi Fisika, 2022)
This study aims to determine the level of sound attenuation of Styrofoam material. This research is using a noise meter application Decibel X: dB Sound Level Meter and a sound generator as a sound source. Then Styrofoam as an acoustic material with a thickness of 1 cm; 1.5 cm; 2 cm; 2.5 cm ; 3 cm; 3.5 cm and 4 cm. The average absorption coefficient obtained in this study with a material thickness of 1 cm is 0.023. Then the average absorption coefficient at a thickness of 1.5 cm is 0.031. While the average absorption coefficient at a material thickness of 2 cm is 0.040. Furthermore, the average sound absorption coefficient at a thickness of 2.5 cm and 3 cm has the same value, namely 0.039. Then, the average sound absorption coefficient at a thickness of 3.5 cm and 4 cm also has the same value, which is 0.038. Based on the research that has been done, it can be concluded that sound absorption at frequencies below 1000 Hz occurs significant sound absorption. At frequencies of 200 Hz, 400 Hz, 600 Hz and 800 Hz, the average sound absorption increases from 1 cm to 3.5 cm of Styrofoam thickness. While the thickness of Styrofoam 4 cm on average did not show a significant increase in sound absorption. Styrofoam thickness of 4 cm can effectively absorb sound at a frequency of 1000 Hz only.